Celebrity endorsement, self-brand connection and consumer-based brand equity. Issue 5 (17th August 2015) - Dwivedi, Abhishek; Johnson, Lester W.; McDonald, Robert E.
Abstract : Purpose: – The purpose of this paper is to examine the impact of celebrity endorser credibility on consumer self-brand connection and endorsed brand equity. A conceptual model is developed, positioning consumer self-brand connections as a partial mediator of the effect of endorser credibility on endorsed brand equity. Design/methodology/approach: – A cross-sectional survey of 382 consumers of sports drinks in the USA was conducted to estimate the conceptual model. Stimuli, devised on the basis of a pre-test, involved celebrity–brand pairings in the context of the US non-aseptic sports drinks industry. Structural equation modeling is used as the analytic tool. Findings: – The research model is empirically supported. Celebrity endorsements impact endorsed brand equity via two pathways. First, a direct effect of endorser credibility on endorsed brand equity was observed, which is positively moderated by the degree of consumer-perceived endorser–brand congruence. Second, self-brand connection partly mediates the effect of endorser credibility on endorsed brand equity, supporting an indirect mechanism of brand equity enhancement. Practical implications: – Managers can now consider using celebrities as tools to develop meaningful self-concept-related connections with consumers. Additionally, the results of this study support for the use of celebrity endorsers as direct brand equity-enhancing tools. Originality/value: – This study is among pioneering investigations that examine the self-concept repercussions of celebrity endorsements, suggesting that celebrity endorsers possess the ability to engage with consumers at the self-concept level, in turn, impacting endorsed brand equity. Additionally, this paper examines the direct and indirect mechanisms by which celebrities influence consumer-based brand equity of the endorsed brand.